(untitled) (Nonconventional Technologies Review, 2015)
Nowadays, microwaves are used in more and more applications such as medicine, treatment of materials, thawing, defrosting, transmission of information and many more. New usages for microwaves consist of decontamination and sterilisation of seeds and sensible materials, such as very old books, fabrics, paintings, statues etc. In order to achieve best results without damaging the treated materials and objects, microwaves are to be used very carefully, and the treatment must observe certain parameters, such as heating time, final temperature, rate of heating, uniformity, pulse and pause ratio etc. This paper describes some of the research that has been carried out during the preparation of Mr.Ursu’s doctoral thesis, concerning these special applications of microwave treatments.